Entrepreneurship and Dynamic Capabilities: A Review, Model and Research Agenda* - Zahra, Shaker A.; Sapienza, Harry J.; Davidsson, Per (Journal of Management Studies, 2006)
abstract The emergent literature on dynamic capabilities and their role in value creation is riddled with inconsistencies, overlapping definitions, and outright contradictions. Yet, the theoretical and practical importance of developing and applying dynamic capabilities to sustain a firm's competitive advantage in complex and volatile external environments has catapulted this issue to the forefront of the research agendas of many scholars. In this paper, we offer a definition of dynamic capabilities, separating them from substantive capabilities as well as from their antecedents and consequences. We also present a set of propositions that outline (1) how substantive capabilities and dynamic capabilities are related to one another, (2) how this relationship is moderated by organizational knowledge and skills, (3) how organizational age affects the speed of utilization of dynamic capabilities and the learning mode used in organizational change, and (4) how organizational knowledge and market dynamism affect the likely value of dynamic capabilities. Our discussion and model help to delineate key differences in the dynamic capabilities that new ventures and established companies have, revealing a key source of strategic heterogeneity between these firms.